Imprecision About Body Mechanics When Child Witnesses Are Questioned About Sexual Abuse. Issue 13 (July 2022) - Sullivan, Colleen; George, Suzanne St.; Stolzenberg, Stacia N.; Williams, Shanna; Lyon, Thomas D.
In child sexual abuse cases, a central part of the child's testimony is their description of the abuse episode. However, it is often difficult for children to describe the body mechanics of abuse, and miscommunications are likely to occur. In the present study, we examined questions about the mechanics of abuse in trial transcripts ( N  = 63) to identify sources of miscommunication ( N  = 130) between attorneys and children (5–12 years old, M age at trial = 9.44, SD  = 1.97). We found that both attorneys and children used imprecise language, which led to miscommunication. Specifically, the imprecise use of sexual terminology and the word "touch, " polarity items, broad open-ended questions, anaphora and elliptical questions, and "how" questions led to imprecision in attorneys' questions. Imprecise attorney questions often elicited underinformative answers from children, including misinterpretations of the grain size (i.e., level of detail) requested. In response to these underinformative answers, attorneys at times asked highly focused and leading questions, which led to further miscommunications. Implications and recommendations for future research on how best to elicit details about the mechanics of abuse from children are discussed.